Coupling electrokinetics and iron nanoparticles for the remediation of contaminated soils - Gomes, Helena Isabel Caseiro Rego (2014)
Fundação para a Ciência e a Tecnologia - PTDC/AGR-AAM/101643/2008 NanoDC ; SFRH/BD/76070/2011 ; FP7-PEOPLE-IRSES-2010-269289- ELECTROACROSS